Metodos industriales empleados en fabricas de azucar para el analisis de pequenas concentraciones de sacarosa en los condensados destinados a la alimentacion de calderas de vapor - Skorik, Konstantin; Sanfiel, Francisco; Angulo, Elier (My University, 1986)
Methods and installations are presented in details for analysis of small concentrations of sucrose in condensates intended for steam boilers supply in sugar industry. Analysis is presented of advantages and disadvantages of direct and indirect methods of sucrose determination. Детально розглянуто методи та пристрої для визначення малих концентрацій сахарози в конденсатах, які призначені для живлення парових котлів у цукровій промисловості. Проаналізовано переваги та недоліки прямих і непрямих методів визначення сахарози.
Keywords: sucrose traces; condensates; sucrose determination methods; direct methods; indirect methods; сліди сахарози; конденсати; методи визначення сахарози; прямі методи; непрямі методи